The biological weapons taboo - Bentley, Michelle (Oxford University Press, 2023)
"The non-use of biological weapons has been described as the 'great mystery of biological warfare.' This book solves that mystery by analysing the bioweapons taboo--in the first comprehensive study of the concept. Bioweapons are so vile, obnoxious, and morally abhorrent that they are deemed to be pariah. Biological armaments are not just another weapon in our minds, and actors do not treat them as such. In applying this understanding of biowarfare to what those actors do (or not) in relation to biological violence, this study explains precisely why actors find bioweapons repulsive and how this sentiment is then expressed in the form of political behaviours, including the refusal to engage in biological aggression. Drawing on extensive archival evidence, this book looks back on United States' foreign policy decision-making (particularly in relation to the Geneva Protocol and the Biological Weapons Convention) to demonstrate how and why the taboo has comprised a decisive factor in shaping both biowarfare strategy and political rhetoric--and why the taboo needs to be recognised as a necessary consideration in the study of bioweapons. In analysing a taboo, the book also takes the debate on international norms forward by questioning and challenging the wider analytic comprehension of 'taboo' itself. Rejecting current definitions of the concept as inadequate, the book proposes a new and original model of understanding based on the normative characteristics of disgust, stigmatization, and fetishization"--
Keywords: Genfer Protokoll wegen Verbots des Gaskriegs -- 1925 Juni 17; B-Waffen-Abkommen -- 1971 Dezember 16; Geschichte; Außenpolitik; Biologische Waffe; USA; Biological warfare / United States / History; Biological weapons / United States / History; Biological warfare / Public opinion; Biological weapons / Public opinion; Armes biologiques / États-Unis / Histoire; Biological warfare; Biological weapons; United States; History